Development of core entrustable professional activities linked to a competency-based veterinary education framework. (2nd December 2019) - Molgaard, Laura K.; Chaney, Kristin P.; Bok, Harold G. J.; Read, Emma K.; Hodgson, Jennifer L.; Salisbury, S. Kathleen; Rush, Bonnie R.; Ilkiw, Jan E.; May, Stephen A.; Danielson, Jared A.; Frost, Jody S.; Matthew, Susan M.
Abstract: Purpose: Despite the adoption of competency-based education in some veterinary schools over the past 15 years, only recently has a concerted effort been directed toward this in veterinary education internationally. Methods: In 2015, educational leaders from the Association of American Veterinary Medical Colleges (AAVMC) member schools came together with a strong call to action to create shared tools for clinical competency assessment. Results: This resulted in the formation of the AAVMC Competency-Based Veterinary Education (CBVE) Working Group, which then embarked on the creation of a shared competency framework and the development of eight core entrustable professional activities (EPAs) linked to this framework. Conclusions: This paper will report on the development of these EPAs and their integration with the concurrently-developed CBVE Framework.